Control de trips en freson: empleo de plantas de haba como refugio de poblaciones de antocoridos - Gonzalez-Zamora, J.E.=700 1 Ribes, A.; Meseguer, A.; garcia-Mari, F.
(Es, En)
ilus., 10 ref.
Keywords: FRANKLINELA OCCIDENTALIS; ORIUS; CONTROL BIOLOGICO; FRAGARIA VESCA; HABA; FRESON; PLANTAS-REFUGIO